A contribuição do PIBID no processo de formação do pedagógico - Silva, Janaina Alves da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper seeks to understand the importance of Pibid (Institutional Scholarship Program for Teacher Initiation) in initial formation, more specifically in the pedagogue's formation. The interest for research was motivated by my inclusion in this program, through the interdisciplinary subproject called University and school thinking of interdisciplinary teacher formation: research, reflection and action in which I participated from August 2011 to December 2013. I developed a qualitative survey of bibliographic character, which aims to analyze the theoretical productions in the field of education and that has the focus the Pibid's contribution as well as its potential. For this purpose, I considered the articles located in the Annals of the XVI ENDIPE (National Meeting of Didactic and Teaching Practice) in 2012, in all its themes (Educational policies and impacts at school and in the classroom, Policies of initial formation and continuing formation of teachers and Didactics and teaching practices in contemporary school reality: findings, analysis and propositions). I believe that the research can contribute to rethink the initial formation practices by providing subsidies to the graduated on the teaching career, raising the quality of basic education

Este trabalho busca compreender a importância do Pibid (Programa Institucional de bolsa de Iniciação à Docência), na formação inicial, mais especificamente na formação do Pedagogo. O interesse pela pesquisa foi movido pela minha inserção no referido programa, através do subprojeto interdisciplinar denominado Universidade e escola pensando a formação docente interdisciplinar: investigação, reflexão e ação, no qual participei de agosto de 2011 à dezembro de 2013. Desenvolvi uma pesquisa qualitativa de caráter bibliográfico, que visa analisar as produções teóricas, no campo da educação e que tem por foco a contribuição do Pibid bem como suas potencialidades. Para tal, considerei os artigos localizados nos Anais do XVI ENDIPE (Encontro Nacional de Didática e Prática de Ensino) no ano de 2012, em todos os seus eixos temáticos (Políticas educacionais e impactos na escola e na sala de aula, Políticas de formação inicial e continuada de professores e Didática e práticas de ensino na realidade escolar contemporânea: constatações, análises e proposições). Acredito que a pesquisa pode contribuir para se repensar as práticas de formação inicial, fornecendo subsídios ao licenciando acerca da carreira docente, elevando assim a qualidade da educação básica
Keywords: Programa Institucional de Bolsas de Iniciação à Docência (Brasil); Professores - Formação; Pesquisa qualitativa; Pratica de ensino; Didática; Redação acadêmica